PENGARUH BEBAN KERJA TERHADAP STRES ANGGOTA POLISI - Tugimin Supriyadi; Muthia Mutmainah Salsabilah; Nabila Salsabila Heryani; Thaliani Karina Sevi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2024)
The National Police has a vital function in maintaining security and public order with five main operational functions: intelligence, investigation, community, guidance, traffic, and bhayangkara samapta. Job stress influences police performance, and understanding job stress in the context of the police profession is important for developing effective strestegies and supports. Factors that influence work stress include excessive workload, time pressure, and interpersonal conflict. This research aims to determine the relationship between job demands and work stress among members of the National Police. Qualitative research methods are used to understand individual experiences and perceptions.